Changes in Sexuality and Quality of Couple Relationship During the COVID-19 Lockdown - Panzeri, Marta; Ferrucci, Roberta; Cozza, Angela; Fontanesi, Lilybeth (Frontiers in Psychology, 2020)
The COVID-19 pandemic is heavily influencing people’s general well-being worldwide. Since its outbreak, many studies have explored the population’s general psychological well-being, while only a few studies have addressed how the COVID-19 pandemic and the lockdown are affecting sexuality. Sexual health, an important aspect of general well-being, has relevant consequences on people’s daily lives. Although it is well known that distress can affect sexuality, and it is possible to speculate that the outbreak’s psychological outcomes are affecting the population’s sexual life; recent literature does not explore couples’ sexuality and their relationship quality during the lockdown. The present preliminary research aimed to understand if the Italian population’s sexuality has changed, and if so, how it had changed since the spread of COVID-19, and which variables were influencing couples’ relationship quality during the COVID-19 lockdown. A questionnaire reserved especially for cohabiting couples was designed and distributed online from April 11 to May 5, 2020, the 5th and 8th weeks, respectively, after the start of the lockdown. Of the 124 respondents who completed the online survey, 73% were females. Despite the pandemic’s psychological consequences, when asked directly, most couples responded that they did not perceive any differences in their sexuality. However, some female participants did report a decrease in pleasure, satisfaction, desire, and arousal. The main reasons behind the changes in sexuality in women, therefore, appear to be worry, lack of privacy, and stress. Even when participants seemed to show high levels of resilience, the negative aspects of lockdown could affect their quality of sexual life. This study needs to be completed using qualitative data from online focus groups that have investigated how sexual life has changed and the main needs of couples. All the same, our results will serve to better address population needs and experiences, and provide ad hoc interventions during this unprecedented time of crisis.